2022
DOI: 10.3390/healthcare10081484
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Biomechanical and Physical Function According to Symptomatic and Asymptomatic Acetabular Impingement Syndrome in Young Adults

Abstract: Femoroacetabular impingement (FAI) is caused by hip joint anomalies. Although asymptomatic and symptomatic FAI have been reported in young adults, information on biomechanical and functional characteristics of FAI is rare. We compared the subjective hip score, range of motion (ROM), dynamic balance, and hip strength between symptomatic FAI (FAIsym) and asymptomatic FAI (FAIasym) groups and healthy controls. Participants (n = 307; men: 155, women: 152) were classified according to morphological abnormalities an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Therefore, low dynamic balance in older individuals increases the risk of falls, which affects performance or causes impairment in activity for those involved in sports individuals [ 26 , 27 , 28 ]. Dynamic balance was low in this study, which was similar to the results of other studies showing a decrease in dynamic balance in patients with hip joint lesions [ 29 , 30 , 31 ]. Single-leg balance ability was reduced in patients with chondropathy, such as soft tissue injury of the hip joint and arthritis [ 31 ], and a study of the dynamic balance of patients with impingement syndrome, as in this study, also showed a significant decrease in the posteromedial and posterolateral directions than in the anterior direction [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, low dynamic balance in older individuals increases the risk of falls, which affects performance or causes impairment in activity for those involved in sports individuals [ 26 , 27 , 28 ]. Dynamic balance was low in this study, which was similar to the results of other studies showing a decrease in dynamic balance in patients with hip joint lesions [ 29 , 30 , 31 ]. Single-leg balance ability was reduced in patients with chondropathy, such as soft tissue injury of the hip joint and arthritis [ 31 ], and a study of the dynamic balance of patients with impingement syndrome, as in this study, also showed a significant decrease in the posteromedial and posterolateral directions than in the anterior direction [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…Single-leg balance ability was reduced in patients with chondropathy, such as soft tissue injury of the hip joint and arthritis [ 31 ], and a study of the dynamic balance of patients with impingement syndrome, as in this study, also showed a significant decrease in the posteromedial and posterolateral directions than in the anterior direction [ 30 ]. In a study where dynamic balance was measured using YBT, the dynamic balance of asymptomatic or symptomatic patients with impingement syndrome was reduced equally [ 29 ]. The background of low dynamic balance in patients with ACH may be neuronal desensitization or sensory information abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations